An approach to innovative software project management in software factories - MARANHÃO, Robson Godoi de Albuquerque (2016)
Innovation has been recognized as an essential condition for gaining competitive advantage, but also for survival in the software industry. The participation of everyone is essential both in idea generation and innovation implementation. Besides the innovation concern, project-oriented software factories are adopting models like CMMI and MPS.Br to achieve an advantage regarding quality. However, the engagement of everyone is sometimes overlooked, so that innovative ideas (incremental innovations) or opportunities for improvement are not perceived. The aim of this study is to build an approach to manage innovative software project (ISPM), guiding project managers and team members in managing innovation in project-oriented software factories. Thus, this approach can be a determining factor in fostering innovation and avoiding it to be stifled by stimulating engagement and participation. A mixed method was used to analyze the phenomenon of fostering innovation in project-oriented software factories, composed of a systematic literature review (SLR) and an action research (AR) in a real organization. The SRL analyzed 17 primary studies, from an initial set of 2,827 articles, where impact factors in ISPM were identified, resulting in the initial approach. The action research was conducted in a large international organization of software development, with units throughout Brazil. The final model of the ISPM approach confirmed the positive influence of engagement and participation of everyone on idea generation and innovative behavior project-oriented software factories. Demonstrating that it is possible to innovate in this context and keep following the procedures defined for the organization. In particular, the findings showed that the creation of a motivating and open environment for creativity made feasible the innovation development. The study results provided explanatory power to promote innovation, as well as showed the importance to study such phenomena in the software industry, specifically in project-oriented software factories. Moreover, the approach provided several strategies and recommendations for professionals to foster innovation and avoid it to be stifled.